2022
DOI: 10.1108/jpbm-04-2021-3448
|View full text |Cite
|
Sign up to set email alerts
|

How to generate customer and firm benefits through online game product and brand community engagement – online and offline perspectives

Abstract: Purpose This study aims to provide a conceptual framework for exploring the relationship between online game product engagement and online brand community engagement and how these two types of customer engagement affect subsequent offline benefit for customers and online and offline benefits for firms. This study also investigates the antecedents of online game product engagement from the virtual experience perspective. Design/methodology/approach This study collected data from online gamers in Taiwan. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 101 publications
(165 reference statements)
0
3
0
1
Order By: Relevance
“…The online brand community provides an effective platform for interaction between users, which creates a unique interactive experience for each other (Lusch & Nambisan, 2015). Social interaction refers to the way customers communicate with each other, bringing consumers and brands closer together emotionally, and increasing user engagement, behavior, and willingness to contribute to the community (Chang & Hsu, 2022;Kang et al, 2020). The social function of the online brand community helps to promote the contributions of members, which are manifested in the creation and distribution of content (Tep et al, 2022).…”
Section: Community-related Factorsmentioning
confidence: 99%
“…The online brand community provides an effective platform for interaction between users, which creates a unique interactive experience for each other (Lusch & Nambisan, 2015). Social interaction refers to the way customers communicate with each other, bringing consumers and brands closer together emotionally, and increasing user engagement, behavior, and willingness to contribute to the community (Chang & Hsu, 2022;Kang et al, 2020). The social function of the online brand community helps to promote the contributions of members, which are manifested in the creation and distribution of content (Tep et al, 2022).…”
Section: Community-related Factorsmentioning
confidence: 99%
“…(Bai et al, 2019). Previous research has indicated that favourable SNS experiences are important drivers of tourists' intentions to travel to a destination (Boley et al, 2018), and increase purchase intentions (Chang and Hsu, 2022). Due to its interactive nature, behavioural brand engagement generates follower-brand links, which followers might want to continue with in later days (Dwivedi, 2015), through recommendations and visit intentions (Vivek et al, 2012).…”
Section: Behavioural Brand Engagement and Visit Intentionsmentioning
confidence: 99%
“…During value co-creation activities, the customers discuss and communicate with companies and other customers about products and the platform of a virtual network brings consumers a new shopping experience, which alters their feelings about the corporate entity and the brand and creates a different brand experience (Ul Islam et al, 2017 ). Prior research on brand experience is common in the field of brand management (Chang and Hsu, 2022 ) and interactive communication in virtual sports brand communities changes the brand experience of consumers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%